1996
DOI: 10.1128/mcb.16.5.2128
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-1 Regulates Free Pools of Catenins and Stabilizes APC-Catenin Complexes

Abstract: The Wnt-1 proto-oncogene induces the accumulation of ␤-catenin and plakoglobin, two related proteins that associate with and functionally modulate the cadherin cell adhesion proteins. Here we have investigated the effects of Wnt-1 expression on the tumor suppressor protein APC, which also associates with catenins. Expression of Wnt-1 in two different cell lines greatly increased the stability of APC-catenin complexes. The steady-state levels of both catenins and APC were elevated by Wnt-1, and the half-lives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
237
1
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(258 citation statements)
references
References 30 publications
19
237
1
1
Order By: Relevance
“…Stable expression of several Wnt genes, including Wnt-1 and Wnt-3a, stabilizes b-catenin in mammalian cells (Hinck et al, 1994;Papko et al, 1996;Shimizu et al, 1997). We also observed soluble Wnt-3a proteins secreted into the culture medium have the same action on b-catenin (Shibamoto et al, 1999).…”
Section: E Ect Of Raxin On Wnt-3a-induced Accumulation Of B-cateninmentioning
confidence: 99%
See 2 more Smart Citations
“…Stable expression of several Wnt genes, including Wnt-1 and Wnt-3a, stabilizes b-catenin in mammalian cells (Hinck et al, 1994;Papko et al, 1996;Shimizu et al, 1997). We also observed soluble Wnt-3a proteins secreted into the culture medium have the same action on b-catenin (Shibamoto et al, 1999).…”
Section: E Ect Of Raxin On Wnt-3a-induced Accumulation Of B-cateninmentioning
confidence: 99%
“…It has been demonstrated that b-catenin accumulates in SW480 human colorectal cancer cells of which APC is truncated and in AtT20 mouse pituitary and C57MG mouse mammary epithelial cells expressing Wnt-1 and that the low molecular weight complexed b-catenin on gel ®ltration column chromatography increases in these cells (Munemitsu et al, 1995;Papko et al, 1996). When the extracts of wild-type L cells were applied to a gel ®ltration column, most of the b-catenin eluted with a peak at fractions 17/18 (high molecular weight complex), while a small amount of b-catenin eluted with a peak at fraction 26/27 (low molecular weight complex) (Figure 4).…”
Section: E Ect Of Raxin On Wnt-3a-induced Accumulation Of B-cateninmentioning
confidence: 99%
See 1 more Smart Citation
“…When the APC protein binds to b-catenin, it promotes the phosphorylation of highly conserved serine and threonine residues in bcatenin's NH2 terminus by GSK-3, thereby targeting b-catenin for degradation via the proteosome system (Papko et al, 1996;Orford et al, 1997). Loss of APC function results in nuclear accumulation of b-catenin, which acts as a transcriptional activator by binding to the Tcf ± Lef (T cell factor/lymphoid enhancer factor) family of transcription factors, ultimately leading to loss of cellular growth control (Morin et al, 1997;Sparks et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The binding of wnt to its receptor frizzled, results in the inhibition of GSK activity (Cook et al, 1996) and a subsequent elevation in b-catenin level (Papko et al, 1996). This is followed by the translocation of bcatenin into the nucleus and its interaction with LEF/ TCF family transcription factors (Behrens et al, 1996;Huber et al, 1996;Molenaar et al, 1996), leading to the transactivation of LEF/TCF-responsive target genes (Molenaar et al, 1996;van de Wetering et al, 1997).…”
Section: Introductionmentioning
confidence: 99%